Hierarchical microtextures embossed on PET from laser-patterned stamps - Bouchard, Felix (2021)
Nowadays, the demand for surface functionalized plastics is constantly rising. To address this demand with an industry compatible solution, here a strategy is developed for producing hierarchical microstructures on polyethylene terephthalate (PET) by hot embossing using a stainless steel stamp. The master was structured using three laser-based processing steps. First, a nanosecond-Direct Laser Writing (DLW) system was used to pattern dimples with a depth of up to 8 µm. Next, the surface was smoothed by a remelting process with a high-speed laser scanning at low laser fluence. In the third step, Direct Laser Interference Patterning (DLIP) was utilized using four interfering sub-beams to texture a hole-like substructure with a spatial period of 3.1 µm and a depth up to 2 µm. The produced stamp was used to imprint PET foils under controlled temperature and pressure. Optical confocal microscopy and scanning electron microscopy imaging showed that the hierarchical textures could be accurately transferred to the polymer. Finally, the wettability of the single- and multi-scaled textured PET surfaces was characterized with a drop shape analyzer, revealing that the highest water contact angles were reached for the hierarchical patterns. Particularly, this angle was increased from 77° on the untreated PET up to 105° for a hierarchical structure processed with a DLW spot distance of 60 µm and with 10 pulses for the DLIP treatment.